Revolution of Malaysia’s Kaolin to Metakaolin towards various application: A mini review - Norsuhailizah, Sazali; Zawati, Harun; Tijani, Abdullahi; Faiz Hafeez, Azhar; Norazlianie, Sazali (Penerbit UMP, 2019)
The transformation of kaolin to metakaolin was studied in various state in Malaysia which is Segamat, Nitar, Lenggor, Ipoh, Bidor, Mersing, Sabah, and Sarawak. In Segamat, the kaolin has a light colour due to the high silicate composition and also contain high mineral such as kaolinite and quartz existed as impurities. Aluminum rich kaolin is bright in color with elevated plasticity and is commonly used in the ceramic, plastic, dye, fabric, pesticide, pharmaceutical and beauty industry. For Nitar and Lenggor, production of metakaolin occurs at 510°C and formation of mullite occur at 900°C. Both clays show good crystallization of pseudohexagonal to hexagonal kaolinite particles. Moreover, the classification of clay and the sizing are the significant characteristic to be determined using the method of the beneficiations. The method of beneficiations is crucially important to increase the quality of clay to meet the requirement for industry application. In Ipoh and Sarawak, the primary deposit is dominated by kaolin and the mixture of granites and diorites produced from weathering. On the other hand, in Bidor, the primary deposit is a mixture of kaolinite, muscovite and smectite also formed by weathering. The increasing amount of illite in secondary kaolin deposits in the Mersing area due to the marine deposition of those deposits where illite formed by the absorption of clay minerals from the seawater by pottasium. Kaolin in Kg Gading, Bongawan Sabah were treated with sodium hexametaphosphate to remove impurities in natural kaolin. The transformation of kaolin to metakaolin was conducted at 800°C for 5 hours.